Realistic mathematics education: An approach to improve problem solving ability in primary school - Lutfi Putri Nugraheni; Marsigit Marsigit (Journal of Education and Learning (EduLearn), 2021)
Mathematical problem solving was an crucial skill to be mastered by primary school student so that will help student to unravel their problems encountered in everyday life. By using the realistic mathematics approach, students learn mathematical concept based on reality or scope around students. This study aimed to develop an eligible learning materials and test the effectiveness of learning materials based on realistic mathematics education to enhance the problem solving skill of primary school students. This research and development study was conducted in Sawangan Subdistrict, Magelang Regency, Central Java, Indonesia. The testing subjects consisted of 12 students in the the preliminary field, there were 42 students in the main field, and 90 students in the operational field that divided into experiment and control class. The data were collected by interviews, observation, and tests. The analyzing N-gain score and t-test with a significant level of 0.05 done to find out th effectiveness of the teaching materials. The developed of realistic mathematics eduation learning materials is feasible and effective in improving problem solving skill with significance value of 0.000 (p≤0.05). It can enhance the problem solving skills of 4th grade elementary school.